Status of agricultural economics in selected countries in Eastern and Southern Africa - Obwona, Marios; Norman, David (International Food Policy Research Institute, 2001)
With more than two-thirds of the population living in rural areas and dependent (directly or indirectly) on agricultural activities for employment and incomes, agricultural growth and development are essential for the reduction of poverty and hunger in Sub-Saharan Africa. Yet, agriculture's potential has not been fully tapped. The need for improved capacity to contribute to more effective policies and policymaking is more pronounced than ever before. Concerned about the continued supply of the needed capacity, the International Food Policy Research Institute, in collaboration with the Eastern and Central African Program for Agricultural Policy Analysis (ECAPAPA) and the African Economic Research Consortium (AERC) and with support from the Rockefeller Foundation, initiated a review of the status of agricultural economics in the Eastern and Southern Africa region. The study, undertaken by two eminent economists, confirmed that the gap between the demand and supply of agricultural economists in the region is widening. There is an urgent need to strengthen and expand training in agricultural economics to meet the unsaturated demand. To do so, training institutions in the region will have to diversify the content and method of delivery of their training programs to remain relevant to current and future challenges and to cater to the diverse needs in the public sector, private sector, civil society, and research institutions. Different modalities for improving agricultural economics training in the region are proposed.